2008
DOI: 10.2353/ajpath.2008.070620
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin: An Enzyme Candidate to Slow the Progression of Alzheimer's Disease

Abstract: It is well established that the extracellular deposition of amyloid ␤ (A␤) peptide plays a central role in the development of Alzheimer's disease (AD). Therefore, either preventing the accumulation of A␤ peptide in the brain or accelerating its clearance may slow the rate of AD onset. Neprilysin (NEP) is the dominant A␤ peptide-degrading enzyme in the brain; NEP becomes inactivated and down-regulated during both the early stages of AD and aging. In this study, we investigated the effect of human (h)NEP gene tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 72 publications
(81 reference statements)
2
135
1
2
Order By: Relevance
“…For example, from its k cat value in Table 1, a single IgV L -tЈ 5D3 molecule is predicted to digest 4320 A␤ molecules in 3 days at excess A␤ concentration. The enzyme neprilysin has received attention as a potential A␤-clearing AD drug (52). The k cat of neprilysin for A␤ is comparable with the IgVs reported here (53).…”
Section: Discussionsupporting
confidence: 74%
“…For example, from its k cat value in Table 1, a single IgV L -tЈ 5D3 molecule is predicted to digest 4320 A␤ molecules in 3 days at excess A␤ concentration. The enzyme neprilysin has received attention as a potential A␤-clearing AD drug (52). The k cat of neprilysin for A␤ is comparable with the IgVs reported here (53).…”
Section: Discussionsupporting
confidence: 74%
“…The primary effect of IDE is degradation of Aβ polymers and fibers Qiu and Folstein 2006), while NEP is used predominantly in degradation of Aβ monomers and oligomers (El-Amouri et al 2008). Our results show that IDE content in the hippocampus of APP/PS1 mice clearly decreases, whereas NEP levels do not differ from those in WT controls.…”
Section: Discussionmentioning
confidence: 54%
“…The results of these therapeutic studies showed reduced plaque pathology and memory improvements in treated animals. 21,[27][28][29][30][31][32][33][34][35] However, because current approaches could ultimately be ineffective or produce unwanted side effects, 36 -38 more tools are always welcome in the search for therapies for AD, and exploration of the potential of NEP2 as a therapeutic agent is warranted.…”
Section: Discussionmentioning
confidence: 99%